New Olivine Reference Material for In Situ Microanalysis. Issue 3 (5th June 2019) - Batanova, Valentina G.; Thompson, Jay M.; Danyushevsky, Leonid V.; Portnyagin, Maxim V.; Garbe‐Schönberg, Dieter; Hauri, Erik; Kimura, Jun‐Ichi; Chang, Qing; Senda, Ryoko; Goemann, Karsten; Chauvel, Catherine; Campillo, Sylvain; et al.
Abstract : A new olivine reference material – MongOL Sh11‐2 – for in situ analysis has been prepared from the central portion of a large (20 × 20 × 10 cm) mantle peridotite xenolith from a 0.5 My old basaltic breccia at Shavaryn‐Tsaram, Tariat region, central Mongolia. The xenolith is a fertile mantle lherzolite with minimal signs of alteration. Approximately 10 g of 0.5–2 mm gem quality olivine fragments were separated under binocular microscope and analysed by EPMA, LA‐ICP‐MS, SIMS and bulk analytical methods (ID‐ICP‐MS for Mg and Fe, XRF, ICP‐MS) for major, minor and trace elements at six institutions world‐wide. The results show that the olivine fragments are sufficiently homogeneous with respect to major (Mg, Fe, Si), minor and trace elements. Significant inhomogeneity was revealed only for phosphorus (homogeneity index of 12.4), whereas Li, Na, Al, Sc, Ti and Cr show minor inhomogeneity (homogeneity index of 1–2). The presence of some mineral and fluid‐melt micro‐inclusions may be responsible for the inconsistency in mass fractions obtained by in situ and bulk analytical methods for Al, Cu, Sr, Zr, Ga, Dy and Ho. Here we report reference and information values for twenty‐seven major, minor and trace elements. Abstract : Olivine grains from a mantle xenolith were analysed by EPMA, LA‐ICP‐MS, SIMS, ID‐ICP‐MS, ICP‐MS and XRF in 6 institutions worldwide. 120 olivine grains tested showed uniform mass fractions of all elements except phosphorus. Well‐characterised reference values were obtained for major (Si, Mg, Fe), minor (Ni, Mn) and trace elements (Li, Na, Al, Ca, Sc, Ti, V, Cr, Co, Cu, Zn, Y, Er, Tm, Yb, Lu).